RESERVE VENDING MACHINE FOOD WASTE SEBAGAI DEPOSITO MELALUI QRIS BANK SAMPAH RUMAH TANGGA - Khairunisa Hilyati; Windu Gata; Eni Heni Hermalani; Achmad Bayhaqy; Frieyadie Frieyadie (JURNAL ILMIAH INFORMATIKA, 2022)
The problem of waste is one of the things that need to be considered by society, especially food waste. Household waste management has begun to be carried out using the Reduce, Reuse and Recycle (3R) method but has not yet used technology. By using Finite State Automata (FSA) which is the basic concept of the Vending Machine (VM), waste management can be more economically by converting waste into balances for Rubbish Bank customers which of course becomes income for the society. In the payment method, QRIS applies where the customer does not get cash but immediately gets the balance which will go into the customer's own account. This implementation certainly reduces the amount of waste because it applies paper less and cashless. In this Reserve Vending Machine Food Waste process using Non-Deterministic Finite Automata (NFA).